Internalisasi Nilai-Nilai Keberlanjutan dalam Film Gerakan Sadar Energi: Pulau Bintang sebagai Media Transformasi Education for Sustainable Development (ESD) - Aldi Firnanda; Lutviatul Mukarromah; Novia Shafa Dwijayanti; Moh. Da’i; Naqi’ah (IAIN Madura, 2026)
This study was motivated by the importance of learning media that integrates Education for Sustainable Development (ESD) values to build students’ energy awareness and ecological responsibility. It aims to analyze the construction of energy awareness—covering solar energy, biogas, water wheels, and electric bicycles—and to identify the representation of ESD values in the film Gerakan Sadar Energi: Pulau Bintang (Energy Awareness Movement: Star Island). Using a qualitative approach with content analysis, the study examined dialogues, scenes, and visual symbols through note-taking techniques. The results show that the film presents the use of solar energy, water wheels, electricity-generating bicycles, and biogas as sustainable energy sources. It constructs energy awareness through concrete and participatory experiences linking human actions to environmental sustainability. The film’s visual and narrative representations integrate cognitive, affective, and behavioral dimensions, making it a potential learning medium to support reflective and sustainable ESD implementation in formal education.